The FoxO Family in Cardiac Function and Dysfunction - Ronnebaum, Sarah M. (2010)
The Forkhead family of transcription factors mediates many aspects of physiology, including stress response, metabolism, commitment to apoptosis, and development. The Forkhead box subfamily O (FoxO) proteins have garnered particular interest due to their involvement in the modulation of cardiovascular biology. In this review, we discuss the mechanisms of FoxO regulation and outcomes of FoxO signaling under normal and pathological cardiovascular contexts.